Imaging Subsurface Fracture and Void using Wide-Band Inversion of Fresnel Interpolated Wavepath Seismic Tomography - Bagus E. B. Nurhandoko (Indonesian Journal of Physics, 2009)
Studying existence of fracture, void as well as fault in subsurface are important and it has wide applications. In addition, fracture and void play important role in reservoir productivity as well as in geotechnical application. The problem in imaging fracture and void in subsurface, however, is resolution. It needs high-resolution imaging method laterally as well as vertically. The seismic velocity imaging, however, usually has poor lateral resolution. Seismic tomography provides better resolution than conventional velocity analysis methods. Conventional raypath seismic tomography, however, needs dense as well as high angle and wide measurement configuration that is high cost in field data acquisition. I propose to use Fresnel interpolated wavepath (FIW) wide-band inversion. FIW is an interpolation between imaginary part of Rhytov scattering wavepath and raypath. Then, FIW is combined with wide band inversion procedure to handle sparseness configuration of measurement. By this method, smooth constraint is implemented more naturally by based on wave's spectrum. Furthermore, it can produce more stable inversion procedure. In this paper, Wide-band inversion of FIW tomography is tested into various seismic field data in order to image void, fault and fracture. The results showed that tomography based on FIW could handle the limitation of configuration angle, sparseness configuration and resulting good image. We use many difficult cases of field data such as: subsurface tunnel imaging and also void-fracture imaging in volcanic rock